EL-MADKOURI MAATAOUI, Mohamed. Lingüística aplicada a la traducción. Madrid: Síntesis, 2020. ISBN: 978-84-1357-042-6. ISBN: 978-84-1357-583-4. 231 pp. - Penas Ibáñez, Azucena (Alfinge. Revista de Filología, 2023)
Reseña de El-Madkouri Maataoui, Mohamed. Lingüística aplicada a la traducción. Madrid: Síntesis, 2020. ISBN: 978-84-1357-042-6. ISBN: 978-84-1357-583-4. 231 pp.